Comparison of Maternal and Fetal Complications in Booked and Unbooked Mothers Presenting in Third Trimester - Ashraf, Viqar; Momina, Shehzad Bashir; Shahid, Sobia (Pakistan Armed Forces Medical Journal, 2022)
Objectives: To see the difference of obstetrical complications along with feto maternal outcomes in both booked and unbooked pregnant cases and to determine the correlation of maternal and fetal outcomes with ante natal care. Study Design: Prospective observational study. Place and Duration of study: Combined Military Hospital Hyderabad and Lahore, from Jan to Jun 2017. Methodology: A total of 900 pregnant cases were included in this study. Out of which 450 were booked cases and 450 were unbooked cases according to WHO definition. Those who have had at least three ante natal care visits at our hospital were labeled as booked cases and those who have had less than three or no ante natal care visit or presented for the first time for delivery to our hospital were labeled as un-booked cases. Results: The majority of pregnant women were found to be between 18–24 years. Maximum number of un-booked cases (72.6%) belongs to illiterate and poor family background. The frequency of anemia and spontaneous vaginal delivery in this study was 29.3% and 30.3%, 70/9% and 15.8% in booked and un-booked mothers respectively. Similarly, the frequency of 14.7%, 3.9%, 3.7%. 11.6% for low-birth-weight babies, gestational diabetes mellitus, IUGR, pregnancy induced hypertension was seen in un-booked cases as compared to booked mothers which have frequency of 12.8%, 8.3%, 2.9% and 11.9% respectively.